A virtualized test automation framework: A DellEMC case study of test automation practice. (7th November 2018) - O'Shea, Donna; Ortin, Francisco; Geary, Kevin
Summary: As software development life‐cycles continue to shorten, the need for reliable, maintainable and scalable test automation solutions becomes more and more important. This importance arises as software, test and automation activities occur earlier in the development life cycle with the aim of providing accelerated feedback on the code and software produced. In this environment, infrastructure and development environments are made available earlier to test teams, the demand of which can create environment bottlenecks as software and automation teams also require the same resources at the same time. To help maximize the use of the underlying resources virtualization and cloud based solutions have been proposed. However, at present there is no guidance on how to design and implement a test automation solution that leverages an underlying virtualized infrastructure. In this paper a virtualized test automation framework designed and implemented by DellEMC Software Quality team in Cork, Ireland is presented along with a macro benchmark analysis of its performance over different virtualization environments.